Relación entre desempeño innovador y madurez de capacidades de conocimiento y competencia (2014)
ABSTRACT: The article is aimed at exploring the relationship between innovative performance, understood as product launches for the domestic market, and the maturity of the capabilities of innovation (CI), of knowledge, and of competence in five large companies of the following industries in Antioquia: sausage, alcoholic beverages, sanitary ceramics, appliances, and animal feed. As to the methodology, a questionnaire was administered, and contingency tables were prepared which describe the relationship between innovative production, whether it is inferior, similar, or superior to that of the competition, and the maturity of the capabilities of innovation shown on three levels: Ad hoc and limited, formalized and predictable, and integration, synergy, and autonomy. With respect to the results, innovative production is related to strategic and technological innovation capabilities, such as research focus, and the capture and storage of, and access to data and information. This shows that it is insufficient to enable only technological and engineering aspects, which is the predominant position in scientific literature. Soft variables related to strategy and culture should also be taken into account.